Demographic Analysis - Selected Concepts, Tools, and Applications - Andrzej Klimczuk (IntechOpen, 2021)
Demographic Analysis - Selected Concepts, Tools, and Applications presents basic definitions, practical techniques, and methods, as well as examples of studies based on the usage of demographic analysis in various institutions and economic entities. The volume covers studies related to population distribution, urbanization, migration, population change and dynamics, aging, longevity, population theories, and population projections. It is an asset to academic and professional communities interested in advancing knowledge on diverse populations in various contexts such as public policies, public services, education, and labor markets. The book aims to help students of demography as well as practitioners of other fields of social sciences and people in government, business, and nonprofit organizations.
Keywords: J10; N30; J14; R23; 330; ageing; demography; family structure; migration; population; public health; statistical studies